Paternal effects associated with melanism in Harmonia axyridis (Coleoptera: Coccinellidae): mating sequence asymmetries and interactions with age‐specific maternal effects. (25th May 2018) - Michaud, J.P.; Abdelwahab, Ahmed H.; Canassa, Vinicius F.; Bain, Clint
Abstract : 1. For this study a cohort of melanic Harmonia axyridis males homozygous for the spectabilis allele was produced. These were used to produce four kinds of twice‐mated females, comprising all four permutations of melanic and non‐melanic (succinic) males. A series of 12 larvae were then reared from the first and 10th clutches of each female to compare progeny developmental phenotypes. 2. There were no effects of mating treatment on overall female reproductive performance (preoviposition period, 20‐day fecundity, or egg fertility). 3. Age‐specific maternal effects were evident in progeny developmental phenotypes; larvae of 10th clutches developed more slowly, pupation was shorter, and adults emerged at heavier weights. 4. Paternal effects were superimposed on maternal effects and affected progeny independent of their paternity; melanic males induced slower larval development and slower pupation, but only in 10th clutches and only when they mated second. 5. There was a significant three‐way interaction between male mating treatment, clutch number and progeny phenotype, indicating that progeny developmental responses to (mixed) paternal effects varied depending on their own phenotype and the time elapsed since their mother's last mating. 6. Melanic males mating second obtained a P2 advantage over succinic males, which increased from first to 10th clutch, but the reverse was not true when succinic males mated second. Thus, polyandry in H. axyridis facilitates both genetic and epigenetic competition among males while simultaneously enabling the sharing of predominant paternal effects among the progeny of different fathers. Abstract : Age‐specific maternal effects caused progeny of 10th clutches to have slower larval development, faster pupation, and larger adult size than progeny of first clutches. Paternal effects were superimposed on maternal effects. Melanic males induced slower larval development and slower pupation, but only in 10th clutches and only when they mated second. Melanic males obtained a P2 advantage over succinic males, which increased in proportion from first to 10th clutch, but the reverse was not true for succinic males.